ANALISIS PENGARUH PENGGUNAAN MEDIA CERITA BERGAMBAR TERHADAP MINAT BACA SISWA KELAS IV SEKOLAH DASAR - Siti Khodijah, Alis; Rohani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Indonesia is currently experiencing a crisis in reading interest at the elementary school level, which poses a significant challenge for educators in improving national literacy. This study focuses on examining the impact of using illustrated story media on the reading motivation of fourth-grade students at SDN Pasanggrahan 1. The research employs a quantitative associative method, with data collected through 30 questionnaires consisting of 30 statements. The data were processed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS software. The results confirm a positive and significant influence of illustrated story media on students' interest in reading (P-Values < 0.05). Based on these findings, the utilization of visual media is highly recommended as a strategic approach to strengthen student participation in literacy activities